Effectiveness of a mobile antiretroviral pharmacy and HIV care intervention on the continuum of HIV care in rural Uganda - Bajunirwe, Francis; Ayebazibwe, Nicholas; Mulogo, Edgar Mugema; Eng, Maria; McGrath, Janet; Kaawa-Mafigiri, David; Mugyenyi, Peter; Sethi, Ajay K. (AIDS care, 2020)
Introduction: Adherence to antiretroviral therapy (ART) is critical in order to achieve viral suppression, one of three UNAIDS targets set for achievement before 2020. One of the main barriers to adherence is the long distance between patient residences and healthcare facilities. We designed an intervention, Mobile Antiretroviral Therapy and HIV care (MAP-HC) in rural southwestern Uganda aimed to reduce travel distance and hypothesized that MAP-HC would improve ART adherence and rates of viral load suppression. Methods: The study was conducted at two sites, Kitagata and Itojo Hospitals, and these are public health facilities located in rural southwestern Uganda. Patients who lived >5km from the hospital were provided the option to participate. For each hospital, we identified 4 health centres in the catchment area to serve as site for the mobile pharmacy. Each site was visited once a month to provide ART refills, adherence counseling and treatment of other illnesses. We measured patient waiting time, adherence and viral load suppression before and after the intervention. Results: We conducted baseline assessment among 292 patients at the two hospitals. The mean waiting time at Kitagata Hospital changed from 4.48 hours before the intervention 58 but increased to 4.76 hours after the intervention (p=0.13). The proportion of patients who missed an ART dose in the last 30 days dropped from 20% at baseline to 8.5% at 12 months after the intervention (p=0.009). The proportion of patients with detectable viral load from 19.9% to 7.4% after the intervention (p=0.001). Conclusions: Our study has showed that a mobile pharmacy intervention in rural Uganda is feasible and resulted in improvement in adherence and viral load suppression. Although it did not reduce patient waiting time at the clinic, we recommend a scale-up of this intervention in rural areas where patients face challenges of transportation to the clinic.
Keywords: Antiretroviral therapy; HIV; Uganda; MAP-HC